(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The term sustainability can be stated as the ability to meet the current needs for development without impacting on the future generations abilities to meet with their own needs. The need to encourage sustainable fashion is very essential as it can contribute enormously towards creating a better living scenario for the future generations to come. The study uses non-probabilistic method of sampling in which judgment and convenience sampling is used for collecting data. A structured questionnaire has been designed from the literature review conducted for the study in a 5 Point Likert Type scale. A total of 240 responses have been collected which would be sufficient for conducting statistical analysis such as multiple linear regression. the dominance of the demographic characteristics such as gender, age, income status and employment on the concerns for sustainability in fashion is statistically proven. The need to include demographic aspects when talking on the matter thus is quite crucial. The study have shown that there are four items extracted that can define overall need for sustainable fashion. These four factors are categorised based on their characteristics and are termed as performance expectancy measure, the perceived ease of use, social influence and the utilitarian value. All the factors are important considerations in fashion and now are being found to cause an impact on the sustainable fashion aspect as well. However, the intention to adopt sustainable fashion is found to be affected by only two factor including the social influence and perceived ease of use.